Argumentation Theory and Argumentative Practices: A Vital but Complex Relationship - van Eemeren, Frans H. (Informal Logic, 2017)
To illustrate the development of argumentation theory, the paper traces the journey of the pragma-dialectical theory as it widened its scope, step by step, from an abstract model of critical discussion to the complexities of actual argumentative discourse. It describes how, having contextualized, empiricalized and formalized their approach, pragma-dialecticians are now putting the theory’s analytical instruments to good use in identifying prototypical argumentative patterns in specific communicative activity types in the various communicative domains. This means that they can now start answering the crucial question about the typical characteristics of their discourse asked by interested lawyers, politicians, academics and other practitioners of argumentation.